Comparison of numerical wind modelling on hectometric and km scales at Kvitfjell wind power plant - Rein, Kristine (UiT The Arctic University of Norway, 2023)
Evaluating the performance of numerical weather models (NWMs) is crucial to identify the best choice of model for wind resource assessments. This thesis has investigated how well NWMs with different horizontal resolutions reproduced the wind directions, the wind speeds and the associated power production at a wind power plant located in complex terrain. The evaluated models included NORA3, WRF1km, and AROME Troms and Finnmark (ATF300m) throughout the 9 months from January to September 2022, as well as WRF111m for some case studies of shorter duration. The models were evaluated by comparing the simulations’ results to hub-height wind measurements. ATF300m outperformed the other models in terms of lower errors when considering the time period as a whole, and also for a case with wind directions similar to the main wind direction registered for the park. This could be as a result of the better topographic representation by the model, thereby including terrain induced effects on the wind more accurately such as orographic blocking. However, NORA3 outperformed the other models in terms of lower errors for two cases with wind directions coming from the NW sector. These results may suggest that 3 km grid spacing gives a sufficient representation of the wind fields when the wind is coming from the open ocean and is less influenced by the terrain before entering the park. Another suggestion may be that the coarser spatial resolution of NORA3 provides lower simulated wind speeds which counteracts the overestimation related to the absence of a wind farm parameterization.